Invited Lecture 6: Environmental pollution and male reproductive health - Sharaine Fernando (Wolters Kluwer Medknow Publications, 2020)
Brief Biosketch Prof. Sharaine Fernando is the Dean and Professor of Physiology, Faculty of Medical Sciences, University of Sri Jayewardenepura. She has delivered the A.C.E. Koch Memorial Oration 2015 on "Lead and Cadmium as Male Reproductive Toxicants; the Known and Unknown" at the University of Colombo in the year 2015. She was the former President and co-founder of the South Asian Association of Physiologists (SAAP). Her area of research interest is the Medical and Health profession education and reproductive health. Spermatozoa are unique specialised cells produced in the testis, stored in the epididymis and transferred to another human/animal where it performs its function of fertilization. They are designed to accomplish several consecutive phases, each one independent and highly critical in achieving fertilization. Each step in the process of spermatogenesis, spermiogenesis and release of spermatozoa are very well regulated by neuroendocrine mechanisms. These regulatory mechanisms can be disrupted by exogenous and endogenous factors. Environmental pollution is one of the major contributors to the external factors. Of them, exposure to a myriad of chemicals and physical agents and heavy metals could lead to disturbances in neuroendocrine regulation, immunological defects and structural and functional abnormalities in the reproductive system. The effects of physical agents such as heat, ionising radiation and electromagnetic waves due to environmental pollution are significant. In addition, disruption of testicular thermoregulation and the blood-testis barrier due to many exogenous factors adversely affect male reproductive function. The main function of the male reproductive system is to produce healthy sperm having a head, midpiece and a tail, each structure playing a crucial role in the fertilization process. The head contains DNA/chromatin that needs to be correctly condensed and de-condensed. The midpiece contains the energy-generating mitochondria and the tail has the flagellum transforming energy into movement. Sperm also possess the ability of oocyte recognition, fusion, and intracellular structures and factors affecting early embryo development and division. In addition, the male reproductive system produces steroid hormones and performs the function of deposition of spermatozoa in the female reproductive tract to enable fertilization. All these functions are adversely affected by environmental toxicants. The effects of harmful environmental pollutants are known to cause damage due to exposure during foetal, neonatal peripubertal or adult life. Scientists warn that exposure to some agents may cause a range of effects such as infertility, sexual dysfunction, testicular malignancies and gonadal dysgenesis which may even last for many generations.